Persaingan Obat Produk Industri di Pekanbaru - Simson Samosir; Wahyu Hamidi; Jahrizal ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The research was conducted in the city of Pekanbaru to consumer products of drugs manufactures. This study aims to determine the factors that influence the level competition for drugs industries products in Pekanbaru. The population numbered 937,939 people and a sample of 100 people was determined by the method Slovin. The data used in the Secondary and Primary Data obtained from PT. BERNOFARM-PKU,PT. KIMIA FARMA-PKU, the Central Statistics Agency (BPS) Riau and questionnaires. The analysis method used is descriptive analysis using ordinal scale (Likert Scale) to classify the measured variables in order to avoid errors in determining the outcome of the data. The results showed that the partial variable consumer tastes which consists of the brand, quality, future expectation, packaging and labels, the price of the item itself and the price of other goods greatly affect the city of Pekanbaru in selecting medicine products they use. While consumer income variable does not affect the demand of drugs for people In the city of Pekanbaru. Based on these results it is suggested to the company to keep value of brand equity, quality, reasonable prices and promotions are always held. Besides, it is also expected the company to expand sales outlets drugs product so consumers have no difficulty in finding the products they are looking for. Thus, consumer loyalty to use one brand of drugs it will remain intact.Keywords: Brand Equity, Quality, Future Expectations, packaging and labels.